Penguatan Ekosistem Halal di Indonesia 2024 melalui Klinik Halal: Strengthening the Halal Ecosystem in Indonesia 2024 through Halal Clinics - Adenan, Moh; Cholifah, Umi; Wulandari, Deasy (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The Prosendi Desa is conducted in the Tegal Besar Village, Kaliwates Sub-district, Jember Regency. It holds substantial potential for developing the halal industry towards achieving the Halal Industry Indonesia 2024. This initiative takes place in the administrative city, primarily due to the heightened concern of MSB operators regarding business legality and halal certification, compared to rural areas in other sub-districts of the Jember Regency. The PRA approach aims to enhance the knowledge of business operators and village government advocates. The Implementation Team, as facilitators, provides direct information, socialization, counseling, and assistance to MSB operators to obtain business legality through the Business Identification Number (NIB) and Halal Certification. The proposed solution consists of two phases/years. The first year encompasses The addition of 10 NIBs for MSB operators as identification, The establishment of a "Halal Clinic" at the Village Office for consultations related to products and supply chains of MSBs in the food sector, and Monthly socialization and the publication of a journal indexed in SINTA 4 regarding the "urgency of the village halal clinic in realizing the Halal Industry Indonesia 2024." The second year includes The development of a guidebook or SOP for "self-declaration" halal certification for MSB operators, Assistance in registering halal certification on the sihalal.com website, Support for MSB operators in field verification and document revision, and Monitoring the document flow until the issuance of the halal certificate.